Dual Ionic Pathways in Semi‐Solid Electrolyte based on Binary Metal–Organic Frameworks Enable Stable Operation of Li‐Metal Batteries at Extremely High Temperatures - Minh Hai Nguyen; Nhat Minh Ngo; Byung‐Kook Kim; Sangbaek Park (Advanced Science)
Abstract The rapid development of the electronics market necessitates energy storage devices characterized by high energy density and capacity, alongside the ability to maintain stable and safe operation under harsh conditions, particularly elevated temperatures. In this study, a semi‐solid‐state electrolyte (SSSE) for Li‐metal batteries (LMB) is synthesized by integrating metal–organic frameworks (MOFs) as host materials featuring a hierarchical pore structure. A trace amount of liquid electrolyte (LE) is entrapped within these pores through electrochemical activation. These findings demonstrate that this structure exhibits outstanding properties, including remarkably high thermal stability, an extended electrochemical window (5.25 V vs Li/Li+), and robust lithium‐ion conductivity (2.04 × 10−4 S cm−1), owing to the synergistic effect of the hierarchical MOF pores facilitating the storage and transport of Li ions. The Li//LiFePO4 cell incorporating prepared SSSE shows excellent capacity retention, retaining 97% (162.8 mAh g−1) of their initial capacity after 100 cycles at 1 C rate at an extremely high temperature of 95 °C. It is believed that this study not only advances the understanding of ion transport in MOF‐based SSSE but also significantly contributes to the development of LMB capable of stable and safe operation even under extremely high temperatures.